Evaporation from porous surfaces into turbulent airflows: Coupling eddy characteristics with pore scale vapor diffusion. Issue 12 (16th December 2013) - Haghighi, E.; Or, D.
<x xml:space="preserve">Abstract</x> [1] Evaporative fluxes from terrestrial porous surfaces are determined by interplay between internal capillary and diffusive transport, energy input, and mass exchange across the land‐air interface. Turbulent airflows near the Earth's surface introduce complex boundary conditions that affect vapor, heat, and momentum exchange rates with the atmosphere. The impact of turbulent airflow on evaporation from porous surfaces was quantified using surface renewal theory coupled with a physically based pore scale model for vapor transfer from partially wet surfaces to individual eddies. The model considers diffusive vapor exchange with individual eddies interacting intermittently with a drying surface to quantify mean surface evaporative fluxes. The model captures nonlinearities between surface water content and evaporation flux during drying of porous surfaces, yielding close agreement with experimental results. This new diffusion‐turbulence evaporation model provides a basic building block for improving estimation of field‐scale evaporative fluxes from drying soil surfaces under natural airflows.